2005
DOI: 10.1017/s1481803500013026
|View full text |Cite
|
Sign up to set email alerts
|

Predicting intervention in renal colic patients after emergency department evaluation

Abstract: Objectives:There is no set of prospectively validated criteria to identify the emergency department (ED) patients with renal colic who are most likely to eventually have to undergo an intervention. This study prospectively assessed predictors of intervention in this patient population. Methods: This prospective cohort study included adult patients with renal colic who presented to 2 tertiary care hospital EDs. Patients had an 18-variable data form completed by an emergency physician and a radiological study to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
36
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 38 publications
(62 reference statements)
9
36
2
Order By: Relevance
“…14 However, most importantly, we found that obstruction was not an independent criterion for intervention, which is inconsistent with previous studies reporting an association between intervention and degree of hydronephrosis. [11][12][13] Taylor et al, for example, recently reported a + likelihood ratio (LR) of 1.45 for mild hydronephrosis and 3.05 for moderate to severe hydronephrosis.…”
Section: Discussioncontrasting
confidence: 99%
“…14 However, most importantly, we found that obstruction was not an independent criterion for intervention, which is inconsistent with previous studies reporting an association between intervention and degree of hydronephrosis. [11][12][13] Taylor et al, for example, recently reported a + likelihood ratio (LR) of 1.45 for mild hydronephrosis and 3.05 for moderate to severe hydronephrosis.…”
Section: Discussioncontrasting
confidence: 99%
“…This is in contrast to survey data reporting a preference for ureteroscopy over stent placement previously suggested by survey results. 8 In the nonemergent context URS and SWL were the most commonly performed urological procedures, which confirms previous reports. 8,10 Our study was unique as it followed patients prospectively at multiple centers from presentation in the ED and examined how initial imaging modality affected treatment pattern.…”
Section: Discussionsupporting
confidence: 87%
“…8 In the nonemergent context URS and SWL were the most commonly performed urological procedures, which confirms previous reports. 8,10 Our study was unique as it followed patients prospectively at multiple centers from presentation in the ED and examined how initial imaging modality affected treatment pattern. We found that consultation rates, frequency of intervention and types of procedures did not vary by whether the patient had 229 230 231 232 233 234 235 236 237 238 239 240 241 242 243 244 245 246 247 248 249 250 251 252 253 254 255 256 257 258 259 260 261 262 263 264 265 266 267 268 269 270 271 272 273 274 275 276 277 278 279 280 281 282 283 284 285 286 287 288 289 290 291 292 293 294 295 296 297 298 299 300 301 302 303 304 305 306 307 308 309 310 311 312 313 314 315 316 317 318 319 320 321 322 323 324 325 326 327 328 329 330 331 332 333 334 335 336 337 338 ...…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…[11,12] It can be assessed according to the visual analog scale (VAS) which is a patient self-report on a scale of 0-10. [13] It is usually treated on outpatient basis by the administration of analgesics in the form of NSAID or narcotics, and only few patients require hospitalization. [9,14,15] Hypertension is another complication of SWL.…”
Section: Introductionmentioning
confidence: 99%